Watchers of time eaudiobook - Todd, Charles (Inspector Ian Rutledge Mystery, 2014)
Charles Todd brings his classic mystery series to a new level of intensity and intrigue. The year is 1919, and Ian Rutledge is a fragile yet courageous former soldier searching for his place in a post-war world. Now a Scotland Yard detective, Rutledge is called upon to probe a murder in the small Norfolk town of Osterley- but he soon discovers that the crime may be connected to one of the greatest disasters of all time .